Changes in corticospinal excitability associated with post-error slowing. (November 2019) - Ceccarini, Francesco; Guerra, Silvia; Betti, Sonia; Vergazzini, Alice; Sartori, Luisa; Castiello, Umberto
Abstract: According to available evidence, after making an erroneous decision people tend to slow down on the next decision. This empirical regularity, known as "post error slowing" (PES), has been traditionally interpreted as the result of a conservative response criterion adopted to avoid future errors and it is supposed to be driven by changes in the excitability of the motor system. However, the consequences of errors have been almost exclusively investigated by means of button-press tasks, which have been criticized because of their limited ecological validity and it is still unclear to what extent errors bias the motor system activity during the planning and the on-line control of complex and realistic goal-directed actions. To overcome these potential limitations, in the present study, we investigated the effect of errors on the preparation and execution of the reach-to-grasp movement, one of the most significant daily life actions. In addition to reaction times (RTs), we measured motor-evoked potential (MEP) to explore the influence of errors on corticospinal (CS) excitability, and we applied kinematical analysis to examine the underlying reorganization of the movement following an error. The results of the present study showed that MEPs tend to be reduced after the failure to reach and grasp an object, supporting the traditional interpretation of PES. Furthermore, in addition to RTs, we found that error-reactivity strategically influences the grasping component of the action, whereas the reaching component appears to be impermeable to PES. These findings demonstrate that the error-reactivity is a strong empirical phenomenon, which spreads into the motor system at the level of both movement preparation and execution, even when more realistic and ecologically valid tasks are used.